Comprehensive identification of pathogenic tandem repeat expansions in sporadic amyotrophic lateral sclerosis: advantages of long-read vs. short-read sequencing - Eleonora Sabetta; Karin Rallmann; Jonas Bergquist; Pille Taba; Pille Taba; Abigail L. Pfaff; Abigail L. Pfaff; Bal Hari Poudel; Davide Ferrari; Massimo Locatelli; Sulev Kõks; Sulev Kõks (Experimental Biology and Medicine)
Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disorder presenting progressive weakness of the bulbar and extremity muscles, leading to a wide-ranging clinical phenotype. More than 30 genes have been associated to genetically inherited ALS yet, approximately 85%–90% of ALS cases are sporadic. Short tandem repeats expansions, have recently been found in clinically diagnosed ALS patients and are currently investigated as potential genetic biomarkers. In this paper we compare the investigation of pathological tandem repeat expansions on a group of ALS patients by comparing the standard short-read sequencing (SRS) technique with a long-read-sequencing (LRS) method which has recently become more accessible. Blood samples from 47 sporadic ALS cases were subjected to SRS by Illumina Whole Genome Sequencing. The genome-wide tandem repeat expansions were genotyped using GangSTR, while wANNOVAR was used for variant annotation. Uncertain cases were further explored using LRS. SRS identified pathological expansions in HTT, ATXN2, and CACNA1A genes in one patient, which were not confirmed with LRS. The latter identified large tandem repeat expansions in the C9orf72 gene of one patient that were missed by SRS. Our findings suggest that LRS should be preferred to SRS for accurate identification of pathological tandem repeat expansions.